2022
DOI: 10.1186/s12866-022-02625-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and maternal factors shaping tonsillar microbiota development in piglets

Abstract: Background The palatine tonsils are part of the mucosal immune system and stimulate immune responses through M cell uptake sampling of antigens and bacteria in the tonsillar crypts. Little is known about the development of the tonsillar microbiota and the factors determining the establishment and proliferation of disease-associated bacteria such as Streptococcus suis. In this study, we assessed tonsillar microbiota development in piglets during the first 5 weeks of life and identified the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Recent microbiome studies have confirmed that commensal S. suis colonize the oral cavity of piglets at high abundance [3–5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent microbiome studies have confirmed that commensal S. suis colonize the oral cavity of piglets at high abundance [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and non-clinical strains are, however, found in all clades, showing that pathogenic lineages can colonize the oral cavity of asymptomatic pigs at low abundance and that commensal lineages can invade the host in certain circumstances. Recent microbiome studies have confirmed that commensal S. suis colonize the oral cavity of piglets at high abundance [3][4][5].…”
mentioning
confidence: 95%
“…As well as being an important pathogen, S. suis is a ubiquitous component of the microbiota of the upper respiratory tract of all pigs. It is one of the most common bacterial species on the surface of the palatine tonsil, which is considered its main niche (12). S. suis disease in pigs takes the form of septicaemia with sudden death, meningitis, arthritis, and endocarditis, and most often affects piglets.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and non-clinical strains are, however, found in all clades, showing that pathogenic lineages can colonize the oral cavity of asymptomatic pigs at low abundance and that commensal lineages can invade the host in certain circumstances. Recent microbiome studies have confirmed that commensal S. suis colonize the oral cavity of piglets at high abundance [35].…”
Section: Introductionmentioning
confidence: 99%